Penerapan model problem based learning berbantuan edpuzzle dalam meningkatkan kemampuan pemahaman matematis siswa kelas VII SMP - Nurlaela, Siti; Yuliani, Anik; Novtiar, Chandra (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
Most students consider mathematics to be one of the most challenging subjects. The low level of math comprehension among middle school students is a driving force for this study. The purpose of this study is to improve students' mathematical comprehension skills by utilizing the PBL approach with the help of Edpuzzle. This research method uses quasi-experimentation, which is carried out by taking 2 classes, namely the experimental class and the control class. The subjects in this study are 54 students in grades VII-B and VII-C SMP Dharma Kartini for the 2023/2024 school year. The instrument used is in the form of a description test using indicators of mathematical comprehension ability. The description questions used are 4 questions in social arithmetic material. The data from the study was processed using 2 independent samples using the normality test and the Mann-Whitney test. The results of the analysis showed that the improvement of mathematical comprehension skills of grade VII junior high school students whose learning using the Problem Based Learning model assisted by Edpuzzle was better than that of those using conventional learning.